2016
DOI: 10.1016/j.addr.2016.04.026
|View full text |Cite
|
Sign up to set email alerts
|

New agents for the treatment of drug-resistant Mycobacterium tuberculosis

Abstract: Inadequate dosing and incomplete treatment regimens, coupled with the ability of the tuberculosis bacilli to cause latent infections that are tolerant of currently used drugs, have fueled the rise of multidrug-resistant tuberculosis (MDR-TB). Treatment of MDR-TB infections is a major clinical challenge that has few viable or effective solutions; therefore patients face a poor prognosis and years of treatment. This review focuses on emerging drug classes that have the potential for treating MDR-TB and highlight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
201
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 285 publications
(209 citation statements)
references
References 131 publications
0
201
0
3
Order By: Relevance
“…Recently, the greatest efforts have focused on screening large compound libraries, sourced primarily from pharmaceutical companies, for their inhibitory activity against the bacillus grown under a variety of conditions in vitro (1,2). A significant advantage of this approach is that it identifies molecules that are active against the whole cell, that is, compounds possessing the ability to overcome the formidable intrinsic resistance mechanisms of mycobacteria (3), which include a notoriously impermeable cell wall and active efflux mechanisms, to inhibit an essential metabolic process or cell structural function. However, key limitations of phenotypic screening include the risk of identifying compounds whose activity is contingent on the chosen growth conditions (4), the propensity for so-called "promiscuous" targets in the mycobacterial cell wall to dominate the list of targets discovered through this approach (5), and the fact that the observed inhibition provides no direct insight into the mechanism of action (MOA).…”
mentioning
confidence: 99%
“…Recently, the greatest efforts have focused on screening large compound libraries, sourced primarily from pharmaceutical companies, for their inhibitory activity against the bacillus grown under a variety of conditions in vitro (1,2). A significant advantage of this approach is that it identifies molecules that are active against the whole cell, that is, compounds possessing the ability to overcome the formidable intrinsic resistance mechanisms of mycobacteria (3), which include a notoriously impermeable cell wall and active efflux mechanisms, to inhibit an essential metabolic process or cell structural function. However, key limitations of phenotypic screening include the risk of identifying compounds whose activity is contingent on the chosen growth conditions (4), the propensity for so-called "promiscuous" targets in the mycobacterial cell wall to dominate the list of targets discovered through this approach (5), and the fact that the observed inhibition provides no direct insight into the mechanism of action (MOA).…”
mentioning
confidence: 99%
“…The nitroaromatic group was postulated to undergo bioreduction to a corresponding nitrosoarene which then reacts with an active site cysteine residue in the DprE1 enzyme to form a semimercaptal adduct inactivating the enzyme. 14,35,38 Recent chemical studies on BTZ043 confirmed the postulated reactivity, indicating that thiolates and other nucleophiles induce nonenzymatic reduction of the nitro groups to the corresponding nitroso intermediates. 39 We conducted NMR experiment where equimolar amounts of reduced glutathione (GSH) and triazenide salt 19a were incubated at room temperature in a mixture of DMSO-d6 and phosphate buffer of pH 7.4 (1:1, v/v).…”
mentioning
confidence: 86%
“…#R6#Some 1,3-diaryltriazenes were modified by N-acylation. Nicotinoyl (14), and isonicotinoyl (15) derivatives were tentatively considered as potential multi-target hybrid compounds of 1,3-diaryltriazenes with isoniazid (INH) structures, potentially releasing the isonicotinoyl radical and 1,3-diaryltriazenes. INH is a highly specific first-line TB prodrug, which after activation couples isonicotinoyl radical to NADPH and binds irreversibly to enoylAcpM reductase, blocking cell wall synthesis.…”
Section: Chemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, new drugs need to be developed and existing drugs for anti-TB properties should be reevaluated for their potential efficacy in the treatment of MDR/XDR-TB. In receiving high-income countries, the international community has responded with financial and scientific support, leading to new drugs [85] and regimens in advanced clinical development and an increasingly sophisticated understanding of resistance mechanisms and their application to all aspects of TB control and treatment. In the absence of a preventive vaccine, more effective diagnostic tools, and novel drugs, the control of MDR/XDR-TB will be extremely difficult.…”
Section: Mdr and Xdr-tb Management Issuesmentioning
confidence: 99%